Analysis of Determinants of Labor Force Participation Rate in Bone District - Winda; Madris Madris; Sabir (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2023)
This study aims to analyze the factors that influence the level of workforce participation in the Born Regency. The variables observed in this study were the level of labor force participation as the dependent variable and then economic growth, state minimum wage and average years of schooling as the independent variables. This study used secondary data obtained from the Central Bureau of Statistics and the Human Resources Department of the Bone Regency from 2004 to 2019. The analytical method used was multiple linear regression using IBM SPSS ver 23. The results of this study show that economic growth has a positive and significant effect on Bone Regency labor force participation, state minimum wage has no effect on Bone Regency labor force participation, and grade level has a negative and significant effect on Bourne Regency labor force participation.